Mitochondrial Enzyme Rhodanese Is Essential for 5 S Ribosomal RNA Import into Human Mitochondria - Smirnov, Alexandre (American Society for Biochemistry and Molecular Biology, 2010)
5 S rRNA is an essential component of ribosomes. In eukaryotic cells, it is distinguished by particularly complex intracellular traffic, including nuclear export and re-import. The finding that in mammalian cells 5 S rRNA can eventually escape its usual circuit toward nascent ribosomes to get imported into mitochondria has made the scheme more complex, and it has raised questions about both the mechanism of 5 S rRNA mitochondrial targeting and its function inside the organelle. Previously, we showed that import of 5 S rRNA into mitochondria requires unknown cytosolic proteins. Here, one of them was identified as mitochondrial thiosulfate sulfurtransferase, rhodanese. Rhodanese in its misfolded form was found to possess a strong and specific 5 S rRNA binding activity, exploiting sites found earlier to function as signals of 5 S rRNA mitochondrial localization. The interaction with 5 S rRNA occurs cotranslationally and results in formation of a stable complex in which rhodanese is preserved in a compact enzymatically inactive conformation. Human 5 S rRNA in a branched Mg(2+)-free form, upon its interaction with misfolded rhodanese, demonstrates characteristic functional traits of Hsp40 cochaperones implicated in mitochondrial precursor protein targeting, suggesting that it may use this mechanism to ensure its own mitochondrial localization. Finally, silencing of the rhodanese gene caused not only a proportional decrease of 5 S rRNA import but also a general inhibition of mitochondrial translation, indicating the functional importance of the imported 5 S rRNA inside the organelle.